Distribution of new cases of leprosy in a northeast state (Research, Society and Development, 2022)
Objective: to analyze the distribution of new leprosy cases in a state of northeast between the years 2008 and 2017. Methods: descriptive, retrospective epidemiological study with a quantitative approach, carried out using secondary data from SINAN; population composed of new cases notified between 2008 to 2017. A descriptive analysis was carried out, seeking to outline the variability of the data among themselves. Results: Following the measurement of the data, they were presented in a descriptive way for the absolute and relative frequencies. 3,542 cases were reported in the period. The variables studied were sex, age group, year of diagnosis and clinical characteristics. Of the total, 51.8% were female, and the age group was concentrated between 30 and 39 years old (18.4%). The most prevalent clinical form was multibacillary. The average detection rate was 21.23 new cases for every 100 thousand inhabitants. Conclusion: the study highlights the need for intensification and implementation of leprosy surveillance.